Analysis of Liner Shipping Freight Rates - Wan, Lindy (2008)
Shipping is one of the world's most international business industries which is one of the prime forces responsible for creating a global economy. The most important development of the shipping business was the unitization of goods leading to containerization of the liner shipping industry. The early liner freight market was mainly protected by pricing conferences. However the changes of containerization and industry consolidation and regulations have pushed the system towards exploring other competitive means such as abolishing the conferencing system and enhancing their services.